Food habits of gaur (Bos gaurus gaurus Smith, 1827) and livestock (cows and buffaloes) in Parsa Wild - Chetri, M (Himalayan Journal of Sciences, 2006)
Food habits of gaur (Bos gaurus gaurus) and livestock (cows and buffaloes) have been studied from January to June 1998 in Parsa Wildlife Reserve, Nepal. The study aimed to understand the diet composition and common plant used by gaur and livestock. Gaurs are both grazers and browsers. The diet of gaur comprised of 38 plant species (20 species of grass, 11 species of browse and 7 species of herb and others) and that of livestock comprised of 35 plant species (19 species of grass, 13 species of browse and 3 species of herb and others). A comparative analysis of plants consumption revealed that gaurs are less selective feeder than livestock. A total of 24 plant species (16 species of grass, 6 species of browse and 2 species of herb and others) were common in the diet of gaur and livestock. 7 species of plants (5 species of grass – Cymbopogon sp., Imperata cylindrica, Phragmites karka, Themeda sp., Vetiveria zizanoides; 1 species of browse – Phaulopsis imbricata and 1 species of herb – Piper longum) are comparatively more utilized by both gaur and livestock. Himalayan Journal of Sciences 1(1): 31-36, 2003